TANZANIA: ZANZIBAR - Abeid, Masoud Fadhil (AGUSPATI Research Institute, 2025)
Abstract: This study investigates the impact of airport services externalization on customer satisfaction at Abeid Amani Karume International Airport (AAKIA), Tanzania. Using primary data from 100 respondents collected through structured questionnaires, the research employed descriptive statistics and regression analysis with IBM SPSS version 27. The findings show that both externalized services and service delivery mechanisms significantly influence customer satisfaction, with a strong positive correlation (R = 0.773) explaining 59.8% of the variance (R² = 0.598; Adjusted R² = 0.590) and a low standard error (0.55497). The ANOVA confirmed the model’s significance (F = 72.177, p < 0.001). Externalized services (B = 0.612) demonstrated a stronger effect than service delivery mechanisms (B = 0.147), highlighting the importance of privatized services in enhancing passenger experiences. The study concludes that efficient, high-quality externalized services are crucial for improving customer satisfaction at AAKIA. Recommendations include training staff in empathy and responsiveness, establishing feedback channels, and investing in advanced technologies such as automated check-in systems. Additional measures include reducing wait times, modernizing infrastructure, and ensuring consistent service quality through standardized procedures and continuous training. Robust monitoring of customer satisfaction and further research on externalization practices are also suggested to strengthen loyalty and overall passenger experience.